2021
DOI: 10.3389/fonc.2021.705720
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Lymph Node Dissection May Be Abolished in Patients With Apparent Early-Stage Low-Grade Mucinous and Endometrioid Epithelial Ovarian Cancer

Abstract: ObjectiveTo investigate whether systematic lymph node dissection can confer clinical benefits in patients with apparent early-stage low-grade epithelial ovarian cancer.MethodsPatients with apparent early-stage low-grade epithelial ovarian cancer seen at Peking Union Medical College Hospital from January 1, 2005, to December 31, 2015, were retrospectively enrolled. Patients with other histological types and those who did not receive necessary adjuvant chemotherapy were excluded. Data collection and long-term fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
1
18
1
1
Order By: Relevance
“…In addition, there is no significant difference in prognosis between lymph node sampling and dissection. This result differs slightly from other previous studies, which may be due to the limited size and design of the reported studies (10,11,18). Similarly, age and laterality are independent risk factors, and related studies have confirmed these risk factors (18,19).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…In addition, there is no significant difference in prognosis between lymph node sampling and dissection. This result differs slightly from other previous studies, which may be due to the limited size and design of the reported studies (10,11,18). Similarly, age and laterality are independent risk factors, and related studies have confirmed these risk factors (18,19).…”
Section: Discussioncontrasting
confidence: 89%
“…Age at diagnosis was classified into three groups, patients under 30 years old, patients between 30 and 50 years old, and patients over 50 years old. Regarding the number of lymph node dissections, all patients were divided into two groups, without lymph node dissection and with lymph node dissection, including lymph node sampling (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and lymph node dissection ([?] 20), and the study endpoint was OS, survival to time of death from any cause.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 For RWS, Chen et al found that for patients with early-stage MOC, lymphadenectomy had no significant prognostic benefit. 13 For patients with advanced stage EOC, however, Tatsuyuki Chiyoda et al revealed that the lymphadenectomy was associated with improved OS for patients with advanced stage EOC. 14 This indicated that more studies are needed to explore the effect of lymphadenectomy on the prognosis of patients with MOC, especially advanced-stage patients.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of patients included in the eight studies was 2964, but only 277 patients had early-stage low-grade serous tumors and were considered for the analysis. Seven studies were retrospective series13–19 and one study was a population-based study 20. The accrual time was from 1975 up to 2018.…”
Section: Resultsmentioning
confidence: 99%